Empowerment of The Roadside Communities in Samirplapan Gresik Through Garbage Bank - Khuliyah Candraning Diyanah; Nuzulul Kusuma Putri; Aditya Sukma Pawitra (Darmabakti Cendekia: Journal of Community Service and Engagements, 2019)
Background: The partnership program with the community was held by establishing  a garbage bank and a waste management center in Samirplapan Village, Duduk Sampeyan District, Gresik. Starting with the problem of partners, the large amount of waste generated due to being on the edge of the inter-city connecting road of Gresik- Lamongan that is often passed by many vehicles. The community still has not the knowledge to manage waste becomes more economic value. Purpose: this activity aimed to help the community in utilizing inorganic waste to be more economically valuable through the garbage bank system. While organic waste will be processed in each household into compost using the Takakura method. Methods: This activity ran for 6 months, beginning with the socialization of garbage banks to village communities, technical training, implementation of the garbage bank system, monitoring and evaluation, and development. The targets of this partnership program are PKK (community that focused on woman welfare) and community in Samirplapan village, which are mostly housewives. Results: A Garbage bank in Samirplapan village has been formed with 35 members, participants actively participate in garbage bank activities, and the knowledge of participants has also increased. In addition, participants were given training in handicrafts made from inorganic waste and how to make compost with Takakura. Conclusion: Garbage bank is one form of solution in handling waste problems by applying the principle of 3R (Reduce, Reuse, Recycle) based on community.